Cover Feature: Biochemical Characterization of β‐Amino Acid Incorporation in Fluvirucin B2 Biosynthesis (ChemBioChem 13/2018). (7th June 2018) - Barajas, Jesus F.; Zargar, Amin; Pang, Bo; Benites, Veronica T.; Gin, Jennifer; Baidoo, Edward E. K.; Petzold, Christopher J.; Hillson, Nathan J.; Keasling, Jay D.
Abstract : The cover feature picture shows fluvirucin B2 and the origin of the nitrogen atom within its macrolactam core:l ‐aspartate. The selection or "loading" ofl ‐aspartate as the starting building block in fluvirucin B2 production is mediated by a set of core enzymes that process and prime the polyketide synthase. We demonstrate the promiscuity of the loading pathway: its ability to use a range of amino acids and further illustrate its ability to load different β‐amino acids selectively onto a PKS loading platform. More information can be found in the communication by J. D. Keasling et al. onpage 1391 in Issue 13, 2018 (DOI:10.1002/cbic.201800169 ).